Advancements in synthesis of Molecularly Imprinted Polymer (MIPs) for highly selective alcohol sensors - Wulan Khaerani; Abdullahi Umar Ibrahim; Uji Pratomo; Souvia Rahimah; Irkham; Yeni Wahyuni Hartati (Sensing and Bio-Sensing Research)
Highly selective alcohol detection systems are being developed for use in the food, pharmaceutical and clinical industries, as well as for rapidly growing alcohol fuel sector. Several methods, including chromatography, refractometry, and spectroscopy, have been reported for determining alcohol content in various samples. Molecularly Imprinted Polymer (MIPs) is a highly selective polymer with active recognition sites in the form of cavities that can specifically bind to target molecules, including alcohol compounds. The use of MIPs in combination with alcohol targets is advantageous due to their reusability and high selectivity. Most existing studies have primarily focused on the synthesis of MIPs using large, non-volatile molecular templates. Therefore, this review focuses on the synthesis of MIPs using various types of alcohol as templates and their application in alcohol detection. It covers the definition, key components, synthesis approaches, and different methods of MIP synthesis, as well as the detection of alcohol using conventional techniques and the application of MIPs for alcohol detection in various sample types.